Dampak Sosial PKM di Sumber Nagan Gunungrejo Singosari Malang : Apa Yang Terjadi Di Sini ? - Nurida Finahari; Gatot Soebiyakto; Alfiana Alfiana (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
Sumber Nagan is one of the water sources located in Gunungrejo Village, Singosari District, Malang Regency. This water source has cultural and religious values. The main use of this water source is for bathing, and drinking water sources. Some residents also use the overflow of water to wash. So far, Nagan Source has not been seen as one economic potential. When the PKM Team of Widyagama University of Malang has completed the repair of physical facilities in Sumber Nagan, there are positive comments from visitors and the user community regarding comfort. This turned out to cause side effects in the form of business land disputes among local residents. This phenomenon is discussed in this article because in general this kind of thing does not appear in community service activities. The results of the analysis show that the general assumptions compiled above the perception that the results of activities are things that should be enjoyed together, need to be reviewed. The situational analysis of partners needs to be extended to their potential social impact.